2014
DOI: 10.1371/journal.pone.0110390
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Inheritance Pattern of Erianthus arundinaceus Chromosomes in the Intergeneric Progeny between Saccharum spp. and Erianthus arundinaceus

Abstract: Erianthus arundinaceus is a valuable source of agronomic traits for sugarcane improvement such as ratoonability, biomass, vigor, tolerance to drought and water logging, as well as resistance to pests and disease. To investigate the introgression of the E. arundinaceus genome into sugarcane, five intergeneric F1 hybrids between S. officinarum and E. arundinaceus and 13 of their BC1 progeny were studied using the genomic in situ hybridization (GISH) technique. In doing so, we assessed the chromosome composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 37 publications
3
58
1
Order By: Relevance
“…Therefore, it has been recognized as one of the most important wild species to the genus Saccharum for increasing the narrow genetic basis of modern sugarcane cultivars (Jackson and Henry, 2011). The genetic diversity of E. arundinaceus has been successfully introgressed into sugarcane backgrounds, and a series of genuine progeny have been produced in different backcrossed generations (D’Hont et al, 1995; Piperidis et al, 2001, 2010; Cai et al, 2005; Wu et al, 2014; Huang et al, 2015). The genomic size of E. arundinaceus had been estimated to be about 3.57 Gb per haploid chromosome equivalent (Yan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been recognized as one of the most important wild species to the genus Saccharum for increasing the narrow genetic basis of modern sugarcane cultivars (Jackson and Henry, 2011). The genetic diversity of E. arundinaceus has been successfully introgressed into sugarcane backgrounds, and a series of genuine progeny have been produced in different backcrossed generations (D’Hont et al, 1995; Piperidis et al, 2001, 2010; Cai et al, 2005; Wu et al, 2014; Huang et al, 2015). The genomic size of E. arundinaceus had been estimated to be about 3.57 Gb per haploid chromosome equivalent (Yan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In light of the abundance of sugar and lignocellulosic materials, sugarcane has been used as the most important sugar-producing crop and a renewable substrate source for biofuels (Aguilar-Reynosa et al 2017). Due to interspeci c hybridization involving the frequent utilization of a limited number of parental clones, this has resulted in a narrow genetic base of modern sugarcane cultivars and limited resilience to biotic and abiotic stresses (Wu et al 2014). Thus, it has become an urgent task to remedy the growing concern of a dearth of genetic variation for sugarcane breeders.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic in situ hybridization (GISH) is a powerful cytological tool for identifying the introgression status of alien chromosomes in sugarcane background (Pachakkil et al 2019;Piperidis et al 2010). GISH results of progeny between sugarcane and E. arundinaceus indicated that chromosome transmission was n + n in F 1 , BC 2 , and BC 3 generations, but was 2n+ n in BC 1 generation (Piperidis et al 2010;Wu et al 2014). In addition, chromosome recombination between sugarcane and E. arundinaceus has also been characterized in BC 1 , BC 2 , and BC 3 generations (Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional sugarcane breeding is probably the most difficult job of any crop, due to the fact that sugarcane cultivars (Saccharum spp. hybrids) are highly polyploidy inter-specific hybrids containing 100 to 130 chromosomes [2,3]. The number of chromosomes may vary across geographical areas.…”
Section: Introductionmentioning
confidence: 99%